2019
DOI: 10.1371/journal.pone.0210644
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HIIT and MICT on cardiovascular risk factors in adults with overweight and/or obesity: A meta-analysis

Abstract: ObjectiveThe purpose of this study was to evaluate the effects of high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) on cardiovascular disease (CVD) risk factors in adults with overweight and obesity.MethodsTwenty-two articles were included by searching six databases, the total number of subjects was 620 in these articles. Outcomes were synthesised using a random-effects meta-analysis of the Standardized mean difference (SMD) in CVD risk factors.ResultsHIIT and MICT resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
115
2
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(158 citation statements)
references
References 83 publications
(119 reference statements)
17
115
2
11
Order By: Relevance
“…Our results are in accordance with various studies showing that the application of both HIICT and MICT succeeded in increasing the VO 2max values for subjects with cardiovascular diseases [4,24], as well as in healthy elderly and middle-aged people [38]. Similarly, in line with the better trend shown by HIICT, a meta-analysis showed that HIIT improved VO 2max more than MICT in overweight or obese adults [39]. Despite the fact that our study measured the VO 2max estimated, the tendency of the results was in the same line.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in accordance with various studies showing that the application of both HIICT and MICT succeeded in increasing the VO 2max values for subjects with cardiovascular diseases [4,24], as well as in healthy elderly and middle-aged people [38]. Similarly, in line with the better trend shown by HIICT, a meta-analysis showed that HIIT improved VO 2max more than MICT in overweight or obese adults [39]. Despite the fact that our study measured the VO 2max estimated, the tendency of the results was in the same line.…”
Section: Discussionsupporting
confidence: 92%
“…Although both HIIT and MICT demonstrate beneficial physiological outcomes for active and insufficiently active populations (i.e., not meeting recommended physical activity guidelines) [5][6][7][8][9][10], both types of exercise have potential advantages and disadvantages. HIIT has been regarded as a time-efficient option that may elicit amplified physiological adaptations compared to MICT [3,9].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…Although both HIIT and MICT demonstrate beneficial physiological outcomes for active and insufficiently active populations (i.e., not meeting recommended physical activity guidelines) [5][6][7][8][9][10], both types of exercise have potential advantages and disadvantages. HIIT has been regarded as a time-efficient option that may elicit amplified physiological adaptations compared to MICT [3,9]. Despite this, there is a debate as to whether HIIT is an appropriate training method for insufficiently active individuals due to questions of affective response, motivation levels, self-regulation, and adherence rates in this demographic [11][12][13][14].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
See 1 more Smart Citation
“…Pois, depende da intensidade e do tempo realizado na mesma, para gerar mudanças cardíacas (débito cardíaco) e perfiféricas (consumo de oxigênio e produção de lactato) Laursen, 2013aLaursen, , 2013b. Apesar destas ressalvas, o TIAI é considerado uma estratégia tempo-eficiente para indivíduos saudáveis e doentes, uma vez que inúmeras evidências demonstram melhora de saúde cardiometabólica, com concomitante redução de tempo dispendido na sessão (Little et al, 2011;Gilen, Gibala, 2014;Madsen et al, 2015a;Gilen et al, 2016;Su et al, 2019).…”
Section: O Papel Do Exercício Físico Na Saúde Cardiometabólicaunclassified